An AC magnetometer using automatic frequency switching of a resonant excitation coil for magnetic nanoparticles characterization - Mohd Mawardi, Saari; Mohd Aufa, Hadi Putera Zaini; Hamzah, Ahmad; Nurul Akmal, Che Lah (2018)
An AC magnetometer using a resonant excitation coil is presented for magnetic nanoparticles characterization. An automatic resonant frequency switching of the excitation coil circuit is developed to reduce the measurement time and human contributed errors. A network capacitor consists of 13 different capacitance values is fabricated and controlled by using a relay module and a microcontroller. The resonant circuit of the excitation coil is resonated up to 81.36 kHz to reduce its impedance observed by a current amplifier. The impedance of the resonant excitation coil is evaluated to access the effectiveness of the resonant technique. A first-order differential coil is used to sense the magnetization from a sample and its sensitivity with respect to magnetic moment and frequency is measured. Using the developed system, we measure the complex magnetization of a multi-core iron oxide nanoparticles solution and estimated its hydrodynamic size.